2016
DOI: 10.5539/ijef.v8n8p237
|View full text |Cite
|
Sign up to set email alerts
|

Trade Openness and Real Investment: Is there Asymmetric Cointegration Relationship? Evidence from Jordan

Abstract: The paper attempts to test the long-run asymmetric equilibrium relationships between real investment and trade openness. Using Jordanian data, over the period 1976 to 2014, the study has failed to reject the null hypothesis of no cointegration with threshold at a conventional level of significance among variables. Therefore, cannot find evidence of asymmetry in the relationship between real investment and trade openness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Using monthly time-series data from Jordan (2006Jordan ( -2016, Aljarayesh et al (2018) discovered that interest rates negatively and significantly impact long-term stock prices. Ahmad et al (2010) found in Pakistan that rising interest rates increase business costs, thereby reducing stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using monthly time-series data from Jordan (2006Jordan ( -2016, Aljarayesh et al (2018) discovered that interest rates negatively and significantly impact long-term stock prices. Ahmad et al (2010) found in Pakistan that rising interest rates increase business costs, thereby reducing stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Remittances and Financial Development Following Al-Assaf [24] and Al-Tarawneh [25], the potential asymmetric cointegration relationship between CPY, remittances, and other explanatory variables is examined by extend the analysis taking into account the possibility of having an asymmetric cointegration relationship among variables, employing Enders and Siklos's TAR model. The threshold value is set to be 0 [26].…”
Section: Testing For Asymmetric Relationship Betweenmentioning
confidence: 99%